Practical realization of electronically adjustable universal filter using commercially available IC-based VBDA - Tattaya Pukkalanun; Worapong Tangsrirat; Natchanai Roongmuanpha (My University, 2020)
This paper describes the practical realization of electronically adjustable voltage-mode universal filter with three inputs and single output (TISO) using the commercially available integrated circuit (IC)-based voltage differencing buffered amplifiers (VDBAs). The realization is resistor-less and contains only two VDBAs and two capacitors. The described filter structure can realize all the five standard biquadratic filter functions from the same configuration without needing any component matching criterions. It also exhibits low-output impedance, which enables for easy cascading in voltage-mode operation. Owing to practical VDBA realization, the filter circuit can be easily made electronically tunable with orthogonal o-Q tuning. The effects of the VDBA non-idealities on the filter performance have been analyzed in detail. To prove the theoretical finding, the performance of the studied circuit was also experimentally measured using the operational transconductance amplifier
Keywords: Realization (probability); Operational transconductance amplifier; Electronic filter topology; Electronic filter; Transconductance; Analog and Mixed-Signal Circuit Design